1998
DOI: 10.1161/01.atv.18.8.1266
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation at the ApoA-IV Gene Locus and Response to Diet in Familial Hypercholesterolemia

Abstract: Abstract-Plasma lipid response to dietary fat and cholesterol is, in part, genetically controlled. The apolipoprotein A-IV (apoA-IV protein; APOA4, gene) has been shown to influence the response to dietary changes in normolipidemic individuals. The response to diet in subjects with familial hypercholesterolemia (FH) is also variable, and no studies are available on the influence of APOA4 mutations on dietary response in these subjects. We studied the effect of 2 common apoA-IV genetic variants (Gln 360 3 His a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
(41 reference statements)
1
12
1
Order By: Relevance
“…In the present study, subjects with the ApoA4 360‐1/2 genotype had only slightly smaller responses of LDL‐cholesterol to diet than those with the 1/1 genotype. The present differences in response between subjects with the 1/1 and 1/2 genotype are in line with those observed in some of the previous studies [20,21], albeit that other studies found a larger effect [22–24] or a small opposite effect [25,26]. One of the explanations for the difference in effect‐size is that ApoA4 360‐1/2 polymorphism may affect response in men, but not in women [20,22–24].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, subjects with the ApoA4 360‐1/2 genotype had only slightly smaller responses of LDL‐cholesterol to diet than those with the 1/1 genotype. The present differences in response between subjects with the 1/1 and 1/2 genotype are in line with those observed in some of the previous studies [20,21], albeit that other studies found a larger effect [22–24] or a small opposite effect [25,26]. One of the explanations for the difference in effect‐size is that ApoA4 360‐1/2 polymorphism may affect response in men, but not in women [20,22–24].…”
Section: Discussionsupporting
confidence: 91%
“…Other major KEGG pathways differing between these groups included genes involved in retinol metabolism, genes linked to the proteosome, and genes associated with antigen processing and presentation (Table 4). Genes linked to lipid homeostasis included genes encoding FASN, which is rate limiting in de novo FA synthesis from carbohydrates (19); CD36 a hepatic FA transporter (39); CYP4A1, involved in FA degradation via -hydroxylation (66); and ApoA4, a lipoprotein associated with VLDL secretion (12). Real-time RT-PCR was utilized to analyze differences in expression of mRNAs coding for genes involved in FA homeostasis including those revealed by array analysis of OO and CO groups and to further compare them with gene expression in the 5% EO group (Table 5).…”
Section: Effects Of Dietary Fat-carbohydrate Ratio and Fat Type On Sementioning
confidence: 99%
“…It should be noted that interaction with other genes 41 and environmental factors 42 could also influence the phenotype in FH patients. Pimstone et al 42 have demonstrated that Chinese FH heterozygotes living in Canada exhibit a similar phenotype to that of other FH patients from Western societies, and different to those living in China.…”
Section: Discussionmentioning
confidence: 99%